Florence Nightingale on society and politics, philosophy, science, education and literature - Nightingale, Florence, 1820-1910 (Nightingale, Florence, 1820-1910. Works. 2001, 2003)
Florence Nightingale on Society and Politics, Philosophy, Science, Education and Literature, Volume 5 in the Collected Works of Florence Nightingale, is the main source of Nightingale's work on the methodology of social science and her views on social reform. Here we see how she took her "call to service" into practice: by first learning how the laws of God's world operate, one can then determine how to intervene for good. There is material on medical statistics, the census, pauperism and Poor Law reform, the need for income security measures and better housing, on crime, gender and the famil.